Arabic Grand Speech Competition as a Medium for Curriculum Development in Islamic Boarding Schools at Gontor for Girls Campus 1 - Fairuz Subakir; Agus Yasin; Ahmad Ario Sofian; Nur Fera Khalifah; Nuraeni Rahmawati (Social Science Academic, 2024)
This study examines the role of the Arabic Grand Speech Competition as a medium for curriculum development at Gontor for Girls Campus 1. Using a qualitative educational ethnography approach, the research explores how Arabic speech activities contribute to communicative competence, Islamic character formation, and institutional language culture within the pesantren environment. Data were collected through participant observation, in-depth interviews, and document analysis involving language supervisors, speech mentors, committee members, and participating students from the *kibar* and *shighar* categories. The findings reveal that the competition functions as a living curriculum that integrates performative Arabic learning, language immersion, hidden curriculum, and leadership training into students’ educational experiences. The activities strengthen students’ *maharah kalam* through repeated oral performance, rhetorical practice, and authentic communicative interaction. Furthermore, the integration of *Haflah Tilawah Al-Qur’an* reinforces the spiritual and da‘wah-oriented dimensions of Arabic learning in pesantren education. The study concludes that curriculum development in Islamic boarding schools is culturally constructed through institutional traditions, communal interaction, and language-based educational practices beyond formal classroom instruction. This study contributes theoretically to Arabic curriculum development discourse and practically to communicative and culture-based Arabic learning models in Islamic education.